2021
DOI: 10.1177/19417381211036412
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Beetroot Supplementation on Recovery After Exercise-Induced Muscle Damage: A Systematic Review

Abstract: Context: Beetroots have antioxidant and anti-inflammatory properties, which may help attenuate inflammation and oxidative stress, enhancing recovery from exercise-induced muscle damage (EIMD). Objective: To evaluate the effects of beetroot supplementation on oxidative stress, inflammation, and recovery after EIMD. Data Sources: SPORTDiscus, PubMed, Web of Science, and Scopus databases were searched, and hand-searching was performed by looking to relevant studies that were cited in other studies. Study Selectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 58 publications
0
10
0
2
Order By: Relevance
“…Additionally, beetroot juice has been studied for its potential in treating hypertension, enhancing physical performance, and aiding in post-exercise recovery [ 162 , 163 , 164 ]. Research has shown that consuming 250 mL of beetroot juice, three times, with two servings 24 h and 48 h after completing 100 drop jumps, reduced muscle soreness and decreased performance decline in countermovement jumps caused by eccentric exercise.…”
Section: Optimal Nutrition For Recoverymentioning
confidence: 99%
“…Additionally, beetroot juice has been studied for its potential in treating hypertension, enhancing physical performance, and aiding in post-exercise recovery [ 162 , 163 , 164 ]. Research has shown that consuming 250 mL of beetroot juice, three times, with two servings 24 h and 48 h after completing 100 drop jumps, reduced muscle soreness and decreased performance decline in countermovement jumps caused by eccentric exercise.…”
Section: Optimal Nutrition For Recoverymentioning
confidence: 99%
“…In fact, the International Olympic Committee consensus statement on dietary supplements and high-performance athletes [ 28 ] lists a number of supplements to improve muscle recovery and muscle damage, including beetroot. However, the results of these studies are controversial, with some studies showing a potential beneficial effect and others finding no significant effect [ 29 , 30 , 31 , 32 ]. The present work aimed to ascertain if beetroot consumption has a role on the recovery of oxidative status and muscle damage in ultra-endurance runners.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is extensive scientific evidence that short-term beetroot supplementation can accelerate recovery from muscle damage after physical activity, additional investigation is required to elucidate whether an extended duration of supplementation (spanning a few days prior to and following exercise) could also facilitate the recuperation of indicators related to muscular damage, inflammatory response and oxidative stress [ 31 ]. Interestingly, beetroot is always mentioned among the supplements recommended for ultra-endurance athletes [ 40 ], and, indeed, six of the thirty-two participants in our study reported beetroot intake during the race.…”
Section: Discussionmentioning
confidence: 99%
“…Özellikle son yıllarda pancar suyu tüketiminin sporcularda vazodilatasyonu teşvik etme, hücresel solunumu düzenleme ve kas performansını iyileştirme özellikleri sayesinde sıklıkla kullanılmaya başlayan bir ergojenik destek olduğu bilinmektedir. Pancar suyunun içerisinde yer alan nitratın vücuttaki NO miktarını arttırarak dayanıklılık performansını iyileştirip metabolik adaptasyonu kolaylaştırdığı gözlemlenmiştir [75][76][77]. Kısa süreli pancar tüketiminin sporcularda ergojenik etki gösterdiğini fakat yüksek dozda ve uzun süreli kullanımda farklı yan etkiler ortaya çıkarabileceğini bildirmektedir.…”
Section: Beta Vulgaris Lunclassified
“…Kısa süreli pancar tüketiminin sporcularda ergojenik etki gösterdiğini fakat yüksek dozda ve uzun süreli kullanımda farklı yan etkiler ortaya çıkarabileceğini bildirmektedir. Bu nedenle pancarın vücuttaki potansiyel etkilerini netleştirmek ve dozunu belirlemek için daha fazla çalışmaya ihtiyaç duyulmaktadır [75][76][77].…”
Section: Beta Vulgaris Lunclassified